Medical Students’ Perception Towards Choosing Pathology Program at Jazan University, Saudi Arabia - Alomaish AR; El Hassan LAM; Mahfouz MS; Haidar WN; M Omer HEO (Advances in Medical Education and Practice, 2022)
Abeer Rihan Alomaish,1 Lamyaa Ahmed Mohamed El Hassan,2 Mohamed Salih Mahfouz,3 Wejdan Nasser Haidar,1 Husam-eldin Omer M Omer2 1Faculty of Medicine, Jazan University, Jazan, Saudi Arabia; 2Department of Pathology, Faculty of Medicine, Jazan University, Jazan, Saudi Arabia; 3Department of Family and Community Medicine, Faculty of Medicine, Jazan University, Jazan, Saudi ArabiaCorrespondence: Mohamed Salih Mahfouz, Department of Family and Community Medicine, Jazan University Faculty of Medicine, Jazan, Saudi Arabia, Email mm.mahfouz@gmail.com; mmahfouz@jazanu.edu.saPurpose: The selection of a specific medical specialty is crucial to medical students and is increasingly associated with future job satisfaction and success in the medical field. We aim to evaluate the perception of medical students at Jazan University towards choosing pathology as a future career and the factors influencing their decisions in order to better the employability of graduates and provide information to both the labor force and curriculum designers.Methods: An observational cross-sectional study was conducted among a random sample of (391) students at the faculty of medicine, Jazan University, from the 2nd to 6th year who registered as a formal student in the academic year 2021/2022. Data was collected via (web-based) a self-administered questionnaire because of COVID-19 pandemic. Chi-squared tests and regression analysis were performed.Results: In this investigation, 92.9% of participants responded. Only 16.2% of undergraduates selected pathology as a future career choice. Among the participants who desired to choose pathology as a career, 28.6% preferred hematopathology as a future sub-specialty. Around 16% considered the most crucial reason for not choosing pathology is the preference for direct patient contact. The differences in age groups, academic level, GPA, and educational level of father between respondents who having a desire to choose pathology as a future career were found to be significantly different.Conclusion: Among the respondents involved in this study, only 16.2% were interested in pathology, while 3.1% chose the field as their first future career choice. Our findings can be applied to help undergraduate better prepare for the future and encourage them to apply to the pathology program to address the shortage of pathologists in the area. Qualitative research is a need to explore the perceptions of current pathology residents and the reasons that can encourage them to choose this important specialization as a future career.Keywords: undergraduate, career choice, pathology, digital pathology, medical curriculum, Jazan, Saudi Arabia